1998
DOI: 10.1093/humrep/13.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Should sperm donors be paid? A survey of the attitudes of the general public

Abstract: Gamete donation in assisted reproduction is an accepted treatment option for certain infertile couples. Traditionally, men donating spermatozoa have been paid a nominal fee, whilst women donating oocytes have not. The issue of payment for sperm donors has recently attracted attention following the Human Fertilisation and Embryology Authority's (HFEA) suggestion that such payment may be withdrawn. Prior to the final meeting of the HFEA working party which is examining this issue, here we report the results of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Unpublished research commissioned by the Department of Health in the UK [11] in 2004 (total sample n = 301, aged between 18 and 54) indicated that 10% would definitely consider donating sperm in order to help infertile couples, 35% may consider this, 22% would not consider this and 28% would under no circumstances consider doing this. Another study found that 42% of the general public and 60% of the students would donate sperm [12]. The Canadian survey among 3500 persons found that 26% would be very or somewhat likely to donate sperm [13].…”
Section: Discussionmentioning
confidence: 99%
“…Unpublished research commissioned by the Department of Health in the UK [11] in 2004 (total sample n = 301, aged between 18 and 54) indicated that 10% would definitely consider donating sperm in order to help infertile couples, 35% may consider this, 22% would not consider this and 28% would under no circumstances consider doing this. Another study found that 42% of the general public and 60% of the students would donate sperm [12]. The Canadian survey among 3500 persons found that 26% would be very or somewhat likely to donate sperm [13].…”
Section: Discussionmentioning
confidence: 99%
“…24 Their respondents fell into three groups, the general public, students (potential donors) and infertile patients (potential recipients). The majority of the public were not in favour of payment (58% No, 38% Yes), potential donors were 67% in favour, 29% against, and potential recipients were 52% in favour, 43% against.…”
Section: Survey Of Attitudesmentioning
confidence: 99%
“…The motivations and experiences of (potential) sperm donors (Cook and Golombok, 1995;Lui et al, 1995), the views of the fertility centres (Golombok and Cook, 1994) and of the general public (Lyall et al, 1998;Nuffield Council on Bioethics, 2011) have been investigated, but only a few studies have examined (candidate) recipients' attitudes towards payment. Lyall et al (1998) questioned potential donors (students), recipients (infertility patients) and the general public. They found that, although most of the general public preferred donors not to be paid (58%), 52% of the potential recipients were in favour.…”
Section: Introductionmentioning
confidence: 99%